Wettability effects on phase behavior and interfacial tension in shale nanopores. (15th April 2021) - Feng, Dong; Bakhshian, Sahar; Wu, Keliu; Song, Zhaojie; Ren, Bo; Li, Jing; Hosseini, Seyyed Abolfazl; Li, Xiangfang
Highlight: The critical shift of confined fluids and molecule-wall interaction is correlated. Curvature-dependent effect with different wettability is characterized. The extended Peng-Robinson equation of state model with including the wettability is proposed. The wettability effects on phase behavior and interfacial tension in nanopores are demonstrated. Abstract: Nanoconfinement effects lead to the anomalous phase behavior of hydrocarbons in nanopores. Besides the capillary pressure, the critical properties' shift and curvature-dependent effect are found to be wettability-dependent parameters. In this work, we propose novel methods to correlate the macroscopic contact angle to the critical properties' shift and curvature-dependent effect with an in-depth analysis of the microscopic interactions, including molecule-wall interactions and intermolecular interactions at the liquid-vapor interface. Then, we extend the Peng-Robinson equation of state model to investigate the effects of wettability on the phase behavior and interfacial tension (IFT) of nanoconfined hydrocarbons. Our results show that the nanoconfinement effects are not only dependent on the pore size but also on the wettability of the pore wall. In nonhydrocarbon-wet nanopores, the nanoconfinement effects are limited, and the bubble point pressure (Pb ) and IFT are close to the bulk values. In hydrocarbon-wet nanopores, with the pore radius smaller than 50 nm, the nanoconfinement effects become visible and they are further strengthened as the contact angle decreases. The calculated results suggest that under reservoir temperature for Eagle Ford reservoir with the pore size of 10 nm, the suppression of Pb and IFT with completely oil-wet cases are nearly six-fold and ten-fold higher than that of intermediate-wet cases.